Superfícies orientáveis - Rodrigues, Jamires Ximenes (2017)
This work aims to present the concept of surfaces in Euclidean space and to present examples, starting from simpler cases as two-dimensional surfaces in R3, to general cases of m-dimensional surfaces in Rn. It is an introduction to the differential geometry of surfaces and of fundamental importance in the study of differentiable manifolds. The purpose is to prepare the reader for a connection with Riemannian geometry, an indispensable subject for masters and doctoral students in Mathematics. For a satisfactory understanding of this work it is necessary to be familiar with concepts of multivariable calculus and basic concepts of linear algebra. In addition, the present study presents the notion of orientable surface and non-orientable surface, presenting examples of each of these types of surfaces.